PEMBELAJARAN TARI SIGEH PENGUTEN KELAS X SEMESTER I SEKOLAH MENENGAH ATAS (SMA) WIRATAMA KOTAGAJAH - Nurul Oktavia; Susi Wendhaningsih; Ni Nyoman Wetty (Jurnal Seni dan Pembelajaran, 2013)
The problem in this research is how a process and result of learning sigeh penguten dance at X class in the first periode Senior High School (SHS) Wiratama Kotagajah. The purpose of this research is to describe implementation program of learning made by teacher’s dance of Senior High school (SHS) Wiratama Kotagajah, teacher’s activities to educate student at the dance learning of sigeh penguten, student activities at the dance learning of sigeh penguten and the result of student education after learning process of sigeh penguten dance.This research used cualitative descriptive desain and use cualitative methode. Cualitative descriptive desain is used to describe a process and result of sigeh penguten dance learing at X class first periode of Senior High School (SHS) Wiratama Kotagajah. In a learning there are three case that covered of learning, the first is what a something to learn it’s about a matery of learning, the second is how to learn it’s abaout a strategy is used in a learning process and the third is how to evaluate it’s about a result of learning process. There are four aspect is used to valuate it. The aspects are used to see if in a learning was happening an interaction. A four aspect are learning program, teacher’s learning process, student’s activities and student’s learning result.From the result of this research can see that a learning process included are learning program made by teacher’s dance the average is good (84%), teacher’s learning process the average is very good (90%) and student’s activities the average is good (80%), there are four activities that use to see a student’s activities. There are visual activities, listening activities, motor activities and emotional activities. Beside the three aspect that explained there is one more aspect in this research, the aspect is evaluate the studen’s learning result. This aspect is used to see a student’s ability. From the student’s learning result the value is very good (0%), good (0%), enough (60%), less (40%) dan fail (0%).